PATIENT DETERMINATION FOR ODONTOECTOMY: ANALYSIS MINOR SURGERY CLINIC OF THE DENTAL AND ORAL HOSPITAL PADJADJARAN UNIVERSITY - Handayani, Ratna Dwi; Rodian, Disti Rahayu; Utami, Ulfah; Praptiwi, Yanni Hendriani; Nurjanah, Neneng (Postgraduate Program , Poltekkes Kemenkes Semarang, 2025)
Odontectomy is a curative procedure in the field of dental and oral surgery aimed at extracting impacted teeth. Patients’ decisions to undergo odontectomy are influenced by several factors, including knowledge, education, and economic status. The Dental and Oral Hospital of Universitas Padjadjaran (RSGM Unpad) is a specialized hospital that offers various dental services, including oral and maxillofacial surgery. This study aims to identify the factors influencing patients' decisions to undergo odontectomy at RSGM Unpad. This research is an analytical study with a cross-sectional design. A total of 30 respondents were selected using accidental sampling. The instruments used were questionnaires assessing knowledge level, educational level, economic status, and motivation for decision-making regarding odontectomy. Data analysis was conducted using Kendall's tau correlation test. The analysis of the relationship between knowledge and the decision to undergo odontectomy showed a significance value of 0.119 and a correlation coefficient of -0.269. The analysis of the relationship between educational level and the decision to undergo odontectomy resulted in a significance value of 0.541 and a correlation coefficient of -0.118. Similarly, the analysis of the relationship between economic status and the decision to undergo odontectomy yielded a p-value > 0.05, indicating no significant correlation. The p-value > 0.05 indicates that there is no significant relationship between knowledge level, educational level, and economic status and patients' decisions to undergo odontectomy in the Minor Surgery Clinic at dental and oral hospital Padjadjaran University.